2011
DOI: 10.1117/12.889308
|View full text |Cite
|
Sign up to set email alerts
|

NIR tracking assists sports medicine in junior basketball training

Abstract: We recorded eye movements of eight elite junior basketball players. We hypothesized that a more stable gaze is correlated to a better shot rate. Upon preliminary testing we invited male juniors whose eyes could be reliably tracked in a game situation. To these ends, we used a head-mounted video-based eye tracker. The participants had no record of ocular or other health issues. No significant differences were found between shots made with and without the tracker cap, Paired samples t-test yielded p= .130 for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Eye tracking is an active multidisciplinary research field, which has shown great progress in the last decades in a range of domains including Medicine, Marketing, Psychology and Human factors [Duchowski 2007]. Several experiments have investigated performance of athletes by e.g., identifying differences between novices and experts or training novices based on knowledge of eye movements from experts [Afonso et al 2012;Hayhoe et al 2012;Huttermann et al 2013;Mann et al 2013;Paeglis et al 2011;Pires et al 2013;Pluijms et al 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Eye tracking is an active multidisciplinary research field, which has shown great progress in the last decades in a range of domains including Medicine, Marketing, Psychology and Human factors [Duchowski 2007]. Several experiments have investigated performance of athletes by e.g., identifying differences between novices and experts or training novices based on knowledge of eye movements from experts [Afonso et al 2012;Hayhoe et al 2012;Huttermann et al 2013;Mann et al 2013;Paeglis et al 2011;Pires et al 2013;Pluijms et al 2015].…”
Section: Introductionmentioning
confidence: 99%